2019
DOI: 10.1177/2309499019875172
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional outcomes of a novel transosseous device to treat rotator cuff tears: A minimum 2-year follow-up

Abstract: Purpose: Despite the improvements in the repair equipment techniques of rotator cuff, a gold standard method has not been defined yet and transosseous fixation through deltoid-splitting (mini-open) approach is still regarded as a good option. The primary purpose of this study is to present satisfactory clinical and functional outcomes with a novel transosseous device in full-thickness rotator cuff tear through deltoid-splitting. Materials and Methods: This retrospective study was performed on 70 consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In 2016, Flanagin et al published the successful mid-term results of transosseous repair in 109 patients (24). In our present study and another recent study, we achieved good functional and clinical results using the new transosseous device Sharc-FT in mini-open rotator cuff repair (16). In 2018, Dyrna et al (26) compared this new device (Sharc-FT) biomechanically with suture anchor as a revision option following failed rotator cuff surgeries.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In 2016, Flanagin et al published the successful mid-term results of transosseous repair in 109 patients (24). In our present study and another recent study, we achieved good functional and clinical results using the new transosseous device Sharc-FT in mini-open rotator cuff repair (16). In 2018, Dyrna et al (26) compared this new device (Sharc-FT) biomechanically with suture anchor as a revision option following failed rotator cuff surgeries.…”
Section: Discussionsupporting
confidence: 63%
“…They found that even in revision surgeries, Sharc-FT was a viable option for commonly used suture anchors that provide equivalent fixation properties. Unlike other transosseous methods, this transosseous device has a perforated body that is intended to handle one to four (or more) internal sutures, and it is specially shaped to maximize resistance to tensile strain and to prevent suture-bone interaction (16). Transosseous cortical fixation sutures form a lateral suture with tensile compression within the footprint, greatly increasing weak bone resistance problems, reducing movement at the tendon-footprint interface, increasing fatigue resistance, and homogenizing the load distribution on the footprint, thus optimizing biological recovery (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 10 More recently, Sandow and Schutz 27 described satisfactory functional and anatomical results with a TO repair in an osteoporotic cohort of 15. Similarly, Arican et al 2 described satisfactory clinical outcomes at >2 years in 70 patients treated with TO repair. In a larger randomized controlled trial of 69 patients, Randelli et al 24 described comparable radiologic and functional results at >3 years between arthroscopic anchor-based and TO repair, while the latter was associated with significantly less postoperative pain.…”
Section: Discussionmentioning
confidence: 85%